(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article discusses some aspects of ensuring food security of the population: the problem, tasks and their solution. A review of the situation in the world, regarding food security and measures to eliminate shortcomings in the field of inter-sectoral relations between countries and mechanisms for reducing the negative impact of sharp fluctuations in world market conditions on the supply of food products to the domestic market were carried A proposal is given for further improvement of legal norms aimed at ensuring the rational use of land and water resources in agriculture, achieving a higher share of food products in agricultural products.